2005
DOI: 10.1093/jnci/dji184
|View full text |Cite
|
Sign up to set email alerts
|

Selective Reporting Biases in Cancer Prognostic Factor Studies

Abstract: Selective reporting may spuriously inflate the importance of postulated prognostic factors for various malignancies. We recommend that meta-analyses thereof should maximize retrieval of information and standardize definitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0
5

Year Published

2006
2006
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 217 publications
(159 citation statements)
references
References 112 publications
2
152
0
5
Order By: Relevance
“…Detailed presentation is more appropriate if the issue investigated is of major concern, or if effect estimates vary considerably. 59,186 Pocock and colleagues found that 43 out of 73 articles reporting observational studies contained subgroup analyses. The majority claimed differences across groups but only eight articles reported a formal evaluation of interaction (see item 12b).…”
Section: Explanationmentioning
confidence: 99%
“…Detailed presentation is more appropriate if the issue investigated is of major concern, or if effect estimates vary considerably. 59,186 Pocock and colleagues found that 43 out of 73 articles reporting observational studies contained subgroup analyses. The majority claimed differences across groups but only eight articles reported a formal evaluation of interaction (see item 12b).…”
Section: Explanationmentioning
confidence: 99%
“…That deficits in reporting can affect the outcome of a study has been shown by many studies (Sutton et al, 2000;Chan and Altman, 2005a, b;Chan et al, 2004;Kyzas et al, 2005). Interestingly, no clear standards exist for the reporting of experimental data.…”
Section: Reportingmentioning
confidence: 99%
“…An appropriate assessment of the study's strengths and weaknesses is not possible without this information. There is ample evidence that prediction research often suffers from poor design and bias, and these may also have an impact on the results of the studies and on the models of disease outcomes based on these studies [4][5][6]. Although most prognostic studies published to date claim significant results [7,8], very few translate to clinically useful applications.…”
Section: Introductionmentioning
confidence: 99%